Development and Validation of Analysis Method For Anthraquinone by liquid Chromatography Tandem Mass Spectrometry - Putra, Deddi Prima; Bakhtiar, Amri; Hajatri, Prima (Fakultas Farmasi Universitas Andalas, 2017)
Indonesia is one of the largest tea producer and exporter in the world. However, the European Union has issued Commission Regulation (EU) No.1146/2014 by setting the MRL (maximum residue limit) of anthraquinone in tea at 20 Î¼g/kg, significantly limiting the amount of tea export from Indonesia to the European Union. Viewed from the side of the danger, especially for synthetic anthraquinone that is potential effect of human health then performed an analysis to determine the presence of anthraquinone in Indonesian tea. To find out anthraquinone concentrations in various tea products, anthraquinone was developed and validated analysis method using LC-MS/MS. anthraquinone was extracted from tea sample using dichlormethane with a soxhlet. Black tea and green tea samples were obtained from one of the tea plantation companies.The validated method was used for the determination of anthraquinone residues in black tea and green tea samples. Anthraquinone residues was detect in all of the test samples.